PENGARUH BEBAN KERJA TERHADAP PRODUKTIFITAS KERJA KARYAWAN PADA CV. RIAU PALET PEKANBARU - Hendrayani, Hendrayani (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
The study was conducted on a CV. Riau Palet Pekanbaru. Based on the research background mentioned above, the writer can formulate the problem in this research is how the effect of workload on employee productivity in the CV. Riau Palet Pekanbaru. The purpose of this research was to determine the effect of workload on employee productivity in the CV. Riau Palet Pekanbaru. The data analysis in this research by using descriptive and quantitative methods. Methods descriptive analysis of data by the decomposition of the theories contained in the bibliography, and are associated with the data obtained from the research that will be collected, classified and tabulated then be concluded. And quantitative methods with simpler linear regression techniques. Samples taken in this study was about 40 people, the research results are seen from the calculation can be obtained by simple linear regression equation is as follows: Y = 66.129-0.700Xhasil simple linear regression has a negative direction of the relationship, the meaning is if the independent variable increases, then the variable is bound to decline. Similarly, the results obtained by the workload has a negative direction of the relationship, ie increasing the workload received by the employee will lower the productivity of the employee. This test is used to see whether the independent variables (Workloads have a significant influence on the dependent variable (labor productivity), with 0.05 then t_tabel values obtained for 2024, ie by the formula t_tabel 1/2 α; n-2 = 0.025; 38). Based on the results of simple linear regression equation equation yields had a negative direction of the relationship, then to use t_tabelnya value becomes -2024, it is because it has a negative direction of the relationship. the value of coefficient of determination of 0.503, or 50.3%, which means that the influence of independent variables (workload) on the dependent variable (labor productivity) is equal to 50.3% while the remaining 49.7% is influenced by a miscellany